2008
DOI: 10.1097/opx.0b013e3181783a86
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corneal Edema on Dynamic Contour and Goldmann Tonometry

Abstract: Contact lens-induced corneal edema caused a small underestimation error in IOP measurements by the Pascal DCT, and an overestimation error in Goldmann tonometry measurements. The OPA measurement provided by the Pascal DCT is insensitive to corneal edema-induced changes in corneal properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
3
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
4
23
3
2
Order By: Relevance
“…They used contact lenses for inducing corneal edema, as we did in our study, and reported that the CCT (40.2∼54.1 μm) and the IOP measurements of the GAT (1.5∼2.8 mmHg) increased after 2 hours of wearing contact lenses. In the study using DCT, there was a significant decrease in IOP measurements (-0.7±1.1 mmHg) after wearing contact lenses, as was the case in our study [10]. We couldn't clearly explain the different results on the effect of contact lens-induced corneal edema on the GAT measurements.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…They used contact lenses for inducing corneal edema, as we did in our study, and reported that the CCT (40.2∼54.1 μm) and the IOP measurements of the GAT (1.5∼2.8 mmHg) increased after 2 hours of wearing contact lenses. In the study using DCT, there was a significant decrease in IOP measurements (-0.7±1.1 mmHg) after wearing contact lenses, as was the case in our study [10]. We couldn't clearly explain the different results on the effect of contact lens-induced corneal edema on the GAT measurements.…”
Section: Discussioncontrasting
confidence: 71%
“…However, Hamilton et al recently reported on the effect of contact lens-induced corneal edema on the GAT measurements [8,9,10]. They used contact lenses for inducing corneal edema, as we did in our study, and reported that the CCT (40.2∼54.1 μm) and the IOP measurements of the GAT (1.5∼2.8 mmHg) increased after 2 hours of wearing contact lenses.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly to our results, recent studies demonstrated that contact lenses induce corneal edema and cause statistically significant differences in IOP values with and without contact lens using GAT and DCT. 14,15 In our study, we obtained the highest IOP value with Pascal DCT and the next highest with NCT. GAT measurements were the lowest of all.…”
Section: Discussionsupporting
confidence: 55%
“…15,16,66 It is a useful tool in situations where the clinician suspects inaccurate IOP measurements that could be caused by corneal biomechanical properties. It is particularly accurate in eyes with keratoconus, 20,21,67 corneal edema, 68 and those that have undergone penetrating keratoplasty 21,22,69 and refractive surgery. 25,70 The DCT provides a score (Q) representing the quality of the IOP measure.…”
Section: Dynamic Contour Tonometry -Pascal Tonometer (Smt Swiss Micromentioning
confidence: 99%